Tradable Permits - A. Denny Ellerman; Nick Johnstone; Friedrich Schneider; Alexander F. Wagner; Juan-Pablo Montero; Johann Wackerbauer (CESifo Forum, 2003)
Tradable Permits – a Market-Based Allocation System for the Environment. Tradable Permits and Other Environmental Policy Instruments – Killing one Bird with two Stones. Tradable Permits – Ten Key Design Issues. Tradable Permits with Imperfect Monitoring. Emissions Trading with Greenhouse Gases in the European Union.
Keywords: Q20; 330; Umweltzertifikat; Umweltökonomik; Immissionsschutz; Umweltpolitik; Klimaschutz; EU-Umweltpolitik; Wirtschaftspolitische Wirkungsanalyse; EU-Staaten; Vereinigte Staaten; Environmental economics; Emission control; Environmental policy; Climate protection; EU environmental policy; Economic policy analysis; EU countries; United States